Contribution of Arm Muscle Power and Eye and Hand Coordination to Long Serve Skills in Badminton Players - Nurmalisa, Nurmalisa; Apriani, Leni (Indonesian Journal of Sport Management, 2024)
Arm muscle power is a component of condition that is no less important than other components of physical condition, when carrying out certain work or activities. Because power is a component of physical condition that concerns the components of an athlete when using his muscles and receiving loads within a certain working time. Apart from that, without having good hand-eye coordination skills, individuals will have difficulty learning the basic techniques of badminton, one of which is the long serve. This research is a literature review study, which aims to reveal "the presence or absence of a contribution of arm muscle power and hand-eye coordination to long serve skills in badminton". The data collection technique used in this literature review is by collecting various references and referrals that are relevant to the problem topic being researched, using the Google Scholar database by entering the keywords "contribution of arm muscle power and eye and hand coordination to long serve skills in badminton players." ”. From the results of searching sources in the database, 10 articles were obtained which were published from 2016 to 2022.